BANK DIGITAL SEBAGAI PERADABAN LEMBAGA KEUANGAN SYARIAH DI INDONESIA - Dian Pertiwi; Amin Suyitno; Endang Rochmiatun; Widiya Nur Anisa; Disfa Lidian Handayani (Indonesian Scientific Journal of Islamic Finance, 2023)
This paper is motivated by advances in internet technology in the era of the industrial revolution 4.0 which caused changes in all areas of industry, including the financial services industry. Sharia banking is required to adapt to digital services to meet customer needs so that they change their business model by transforming digitally into digital banks. This type of research is library research with a qualitative descriptive approach that seeks to provide an overview of the civilization and development of Islamic financial institution in Indonesia. The results of this paper explain that the development of digital Islamic financial institutions is growing rapidly, this is a strength possessed by Islamic digital banks which makes it easy to access data that can be accessed via GooglePlay and the App Store. Due to the easy access of Islamic financial institutions digitally, it will be easier for customers to manage their finances, and Islamic financial institutions can enhance partnerships with various parties to develop services that suit customer needs.